Big book to increase 5th grade students’ reading literacy - Dian Permatasari Kusuma Dayu; Niken Dwi Setyaningsih (Jurnal Prima Edukasia, 2022)
This study aims to determine the effect of using big book media on students' reading literacy in class. This research used a quantitative approach. The research design was a pre-experimental one-group pretest-posttest design. Data collection techniques using tests and observations. The data analysis techniques were validity, reliability, normality, homogeneity, t-test, and N-gain tests. The subjects of this study were 50 students of grade V consisting of 35 females and 15 males. The results show that there is a significant effect of big book media on the reading literacy of grade V students in elementary schools. The results of the Statistical analysis of the t-count test is 6.349 t-table 2,0. It can be concluded that big book media, is effective on students reading literacy.